The agreement of the various distance walkway in the 6-minute walk test in healthy adults. - Busaba Chuatrakoon; Natakit Seepang; Derin Chaiwong; Rawes Nanavichit; Kittipan Rerkasem; Sothida Nantakool (PLoS ONE)
Background Despite a practical guideline of 30-meter walking path during 6-minute walk test (6MWT), such walking course length is not possible in every clinical setting due to unavailable sufficient space. Existing evidence has investigated using several shorter course lengths, it remains unclear whether a walking course length shorter than the standard walking course length is appropriate for 6MWD testing. This study aimed (i) to compare maximum walking distances at various shorter walking course lengths (i.e., 10, 20, and 25 meters) and 30 meters, and (ii) to assess agreements in maximum walking distances achieved at intervals below 30 meters, specifically 10, 15, 20, and 25 meters. Methods This study was a cross-sectional with cross-over design. Forty-eight healthy participants were randomly ordered to perform 6MWT with five different walkways (10, 15, 20, 25, 30 meters). The maximum walking distance (six-minute walk distance, 6MWD) covered was recorded. Results Eligible participants aged 41.0 ± 17.2 years, with equal sex (24 males) participated in this study. The 6MWD at 10, 15, and 20-meter walkways significantly shorter than the 30-meter standard walkway (489.6 ± 59.3 m, 513.1 ± 62.6 m, 524.7 ± 63.7 m vs 539.1 ± 63.1 m, respectively (P<0.01)). Very strong agreement was observed at 15, 20, and 25 meters with the standard 30 meters (0.819-0.875, P<0.001). Subgroup analysis showed strong to very strong agreement in 10-meter walkway length onwards with the standard walkway length among older adults (0.757-0.918, P<0.001). Conclusions Testing on 20 meters walkway and shorter yielded varied results compared to the standard 30-meter walk, with exceptional congruence observed at 15 meters onwards. In particular, a minimum walkway of 10 meters had strong agreement with a standard 30-meter walkway in elderly.